The Impact of State Laws on Officer-Involved Deaths (OIDs) - Steele, Morgan J. (Criminology, criminal justice, law & society, 2024)
While the public debates whether law enforcement has a problem with mis- or over-using force, the field lacks critical information concerning how often officers use force when interacting with citizens. Moreover, researchers have not examined how differences in how states restrict officers’ ability to use force affect the frequency of force used. Consequently, the various reforms proposed have little evidence supporting them. Using data from Mapping Police Violence combined with census data, we examined the impact of the incorporation of U.S. Supreme Court jurisprudence and the overall restrictiveness each state placed on law enforcement’s ability to use force when making an arrest and what constituted reasonable force within each state. We found that while the state’s population size and violent crime rate were strong predictors of the number and rate of officer-involved deaths (OIDs), state statutory restrictions on use of force had negligible effects. This has important implications for reforming state and national discussions around reforming use of force.